Midwifery Care on Pregnancy Exercise Support for Mrs. I in the Third Trimester to Reduce Lower Back Pain - Noer Aztika Raditya; Diah Atmarina Yuliani (Proceedings Series on Health & Medical Sciences, 2024)
Background:Discomfort that usually occurs in third trimester pregnant women is frequent urination, soreness or pain, constipation, leg cramps, respiratory problems and edema. Low back pain is one of the discomforts that pregnant women often experience in the third trimester. The growth of the uterus causes the body's center of gravity to shift forward. Therefore, pregnant women need to adjust their standing position. This means that expectant mothers must rely on their muscle strength, deal with weight gain, changes in joint relaxation, fatigue, and also pay attention to their pre-pregnancy posture. The need for pregnancy exercise is very important in strengthening and maintaining the elasticity of the abdominal wall muscles, ligaments and pelvic floor muscles associated with the birthing process. Pregnancy exercise can also help relieve low back pain which is often experienced by pregnant women because it involves movements that strengthen the abdominal muscles. Method: A case study report with descriptive method, location at Mrs. I Pekaja Village Rt 02/03 Kalibagor District Banyumas Regency. The subject of the case study is Mrs. I is 33 years old G2P1A036 weeks gestation with low back pain. The case study time is January 19, 2023. Data analysis from interviews was conducted to collect primary data, and documentation and literature studies were conducted to collect secondary data. Results: In general, Mrs. I was a normal pregnancy, and Mrs. I is a normal thing to happen in the third trimester of pregnancy. Conclusion:Doing pregnancy exercises at least twice a week can reduce pain in the lower back.